Comparative evaluation of flow profile of commercially available vinyl polysiloxane impression materials - An in-vitro study - Midhila Madhusudanan; Vidya K Shenoy; Jalis A Khan; Avinash V Mehendale; Madhu K Bangera (Wolters Kluwer Medknow Publications, 2022)
Background: Flow characteristics of vinyl polysiloxane (VPS) impression materials are important determinants in the selection of impression materials for the fabrication of accurate indirect restorations. Aims: The purpose of this study was to determine the flow of three commercially available VPS impression materials at different time intervals using a shark fin device (3M ESPE, Seefeld, Germany). Study Setting and Design: This in-vitro study was carried out at the prosthodontics department of a dental institution. Methods and Material: The height of the shark fin produced by each impression material determined the rate of flow. Statistical Analysis: The data were analysed using one-way analysis of variance (ANOVA) and post-hoc Tukey's test (p-0.05). Results: Shark fin height of group A VPS impression material was significantly higher at 30 and 120 seconds compared to group B and group C VPS impression materials. Shark fin height produced by group B VPS impression materials at 60 and 90 seconds was significantly higher than the group C VPS impression material but non-significant compared to group A. At 120 seconds, there was no significant difference in the shark fin heights of all the tested materials. Conclusion: All the materials exhibited adequate flow characteristics within clinically acceptable limits.